Can formal banks be a sole facilitator of firm’s financial needs? - A brief outlook on Indian financial sector - Varghese, Thresi (Advances in Social Sciences Research Journal, 2018)
This paper will shed some light on the funding of businesses in India .The financial performance of India's business sector has been under stress since many years. Balance-sheet data on a large cross-section of Indian non-financial businesses show that the growth in their power over the last 15 years has been associated with an outstanding increase in the liabilities of firms carrying high interest payment burdens. Judged by the debt carried by the most exposed component of firms, the Indian corporate sector’s problem to severe systemic shocks has increased to levels not seen since 2001. Progress on the macroeconomic front, together with improved credit evaluations and stricter impairment standards on the bank side, will be critical to help India's banks continue their role as economic growth drivers.